Some Variables Associated with Psychologists’ Appraisal of Psychotherapy in Argentina - García, Horacio Daniel (The Spanish Journal of Psychology, 2005)
The purpose of this research is to provide information about the state of psychotherapy in Argentina, as well as to study some variables involved in psychologists’ evaluation of psychotherapy. A survey of 14 items was elaborated ad-hoc for this purpose, and administered to 226 psychologists from all over the country by mail and, in some cases, personally. Results suggest that the predisposition to apply techniques from different frameworks is associated with the amount of experience and with the perception of a bias concerning other theoretical focuses, although it is not related to the evaluation of the state of psychotherapy. On the other hand, in the view of psychologists, personal aspects of the therapeutic relationship are believed to be the most important factor in patients’ change and effective progress.